Olhares sobre a história de Pirpirituba-Paraíba : uma perspectiva de ensino de história local por meio da educação patrimonial - Silva, Monique Leandro da (2024)
This dissertation addresses teaching practices regarding Heritage Education and the Teaching of Local History through research conducted in the city of Pirpirituba–PB, with a special focus on Monsenhor Walfredo Leal School and Nossa Senhora do Rosário Mother Church, in dialogue with other relevant heritage sites in the city. Recognizing the importance of local themes throughout the final years of elementary education, understanding them as a continuous and integrated process, not limited to the early years, our research was structured with the conviction that students' experiences and their relationship with the community are fundamental throughout the educational journey. The work presents itself as a pedagogical proposal aimed at teaching Local History and Heritage Education, aiming to raise awareness of and value the cultural expressions and memory present in students' everyday lives. It also seeks to contribute to a better understanding of Pirpirituba's history and to stimulate future and necessary research on this local history. The final product is the creation of an Activity Workbook intended for History teachers and related areas, providing guidance on how to incorporate the proposals of this work with high school students, and it can be adapted for any grade in the final years of elementary education. The manual explores the use of pedagogical activities both inside and outside the classroom, aiming to promote a more engaged approach to History teaching with the local context, encouraging students to pay closer attention to the cultural manifestations and identities surrounding them, as well as their appreciation and the development of a solid historical consciousness.